HRIS Model Design (Human Resources Information System) at PT. Poultry Diamond Partners - Carmela Kaloka Putri; Sapta Dwikardana (Journal of Social Research, 2023)
The livestock business is one of the businesses that contribute quite significantly in developing quality human resources for a country. The development of quality human resources must certainly be supported by the adequacy of quality animal food so over the past few years the government has focused on encouraging the growth and development of livestock businesses to strengthen the country's food security. The method used in this research is action research. Methods in action research are based on the assumption that theory and practice can be integrated with learning from the results of planned interventions after carrying out a diagnosis process against the context of the existing problem. Based on the results obtained from the diagnostic stage, PT. Mitra Berlian Unggas currently does not have a standard and effective MSDM management system. With the limited number of members of the HR Division and the existence of a plan to develop and grow the livestock network, the company realized the need for a system that could accommodate "improvement" efforts and facilitate the work of the HR Division in managing employees. HRIS design at PT. Mitra Berlian Unggas is carried out by considering the company's need for the ability of the system to facilitate the management of human resources in the company today, without excluding the characteristics of the company that has a distribution of livestock networks in several regions, so that employees need to work remotely.